Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1002/jac5.1326
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of burnout among emergency medicine pharmacists

Abstract: IntroductionBurnout syndrome is a prolonged response to chronic emotional and interpersonal stressors and is becoming an increasing concern in the medical community. Burnout in emergency medicine (EM) pharmacists has not been previously assessed.ObjectivesTo identify the prevalence of burnout among EM pharmacists, in addition to demographic, professional, seasonal, and job‐related associations.MethodsPharmacists practicing greater than 50% of their time in the emergency department (ED) setting were invited thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…All of the studies were cross-sectional, carried out across eight different countries, the majority from the USA ( n = 11/19), published from 1990 up to 2022, with a total of 11,306 pharmacist participants in patient-facing work environments. Nine studies [ 17 – 20 , 23 , 24 , 27 , 28 , 34 ] investigated pharmacists across multiple professional settings, six studies [ 21 , 26 , 28 , 31 33 ] measured burnout in hospital pharmacists and four studies [ 16 , 22 , 25 , 29 ] investigated community pharmacists. The number of participants in each study ranged from 116–2231.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All of the studies were cross-sectional, carried out across eight different countries, the majority from the USA ( n = 11/19), published from 1990 up to 2022, with a total of 11,306 pharmacist participants in patient-facing work environments. Nine studies [ 17 – 20 , 23 , 24 , 27 , 28 , 34 ] investigated pharmacists across multiple professional settings, six studies [ 21 , 26 , 28 , 31 33 ] measured burnout in hospital pharmacists and four studies [ 16 , 22 , 25 , 29 ] investigated community pharmacists. The number of participants in each study ranged from 116–2231.…”
Section: Resultsmentioning
confidence: 99%
“…Fourteen of the studies [ 17 , 18 , 20 , 21 , 23 , 24 , 26 31 , 33 , 34 ] (73.7%) measured burnout using a version of the MBI. Two studies [ 16 , 22 ] used the CBI and one study [ 29 ] used the Shirom-Melamed Burnout Measure (SMBM).…”
Section: Resultsmentioning
confidence: 99%
“…Within the context of emergency medicine, where up to 69.5% of pharmacists demonstrated burnout, the factors associated with burnout include younger age, increased emergency department visits per year, level I trauma center designation, and lower percentage of direct patient care time. 21 Burnout in this evaluation was associated with intent to leave one's current position or the specialty of EM and consideration of a job with different hours. Within EM, depersonalization was a common manifestation as opposed to emotional exhaustion.…”
Section: Discussionmentioning
confidence: 99%
“…12 The hematology-oncology pharmacist survey found that those with a high degree of burnout were more likely to report concern they had made a major medication error within the past 3 months and expressed intent to leave their current job within 2 years. 13,14 in one study as the greatest contributors to stress. 15 Among pharmacy residents, that some of the factors that contribute most to burnout include fear of error, publication pressure, and the variability of expectations throughout the year (Table 1).…”
Section: Burnoutmentioning
confidence: 94%
“…The EM pharmacist survey found high rates of burnout (67.1%‐69.8%) that was associated with younger age, more trauma center designation, patient volumes, and direct patient care time 12 . The hematology‐oncology pharmacist survey found that those with a high degree of burnout were more likely to report concern they had made a major medication error within the past 3 months and expressed intent to leave their current job within 2 years 13,14 . Other studies have validated the high rates and predictors of burnout among clinical pharmacists.…”
Section: Barriers To Retention and Contributors To Attritionmentioning
confidence: 99%